Mucosal immune responses to treadmill exercise in elite wheelchair athletes - Leicht, C. A.; Bishop, N. C.; Goosey-Tolfrey, V. L. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The study's purpose was to examine salivary secretory immunoglobulin A (sIgA) responses and a-amylase activity after constant load and intermittent exercise in elite wheelchair athletes. Methods: Twenty-three wheelchair athletes divided into three groups (eight tetraplegic (TETRA), seven paraplegic, and eight non-spinal cord-injured) performed two randomized and counterbalanced 60-min sessions on a treadmill. These consisted of constant load (60% peak oxygen uptake) and intermittent (80% and 40% peak oxygen uptake) exercise blocks. Timed unstimulated saliva samples were obtained before, mid, after, and 30 min after exercise and analyzed for sIgA and a-amylase. Furthermore, oxygen uptake, blood lactate concentration, and RPE were measured during both sessions. Results: SIgA secretion rate and a-amylase activity were increased during exercise in all groups (P < 0.05). However, the increase of sIgA secretion rate during exercise was greater in TETRA individuals (postexercise average data for both trials in comparison with preexercise data: TETRA = +60% ± 31%, paraplegic = +30% ± 35%, non-spinal cord-injured = +11% ± 25%; P < 0.05). Yet, groups were comparable with respect to blood lactate concentration and RPE for both exercise sessions. Conclusions: Despite the disruption of autonomic salivary gland innervation in TETRA athletes, their ability to increase sIgA secretion rate seems comparable to wheelchair athletes with intact autonomic salivary gland innervation. The similar responses between groups may stem from sympathetic reflex activity during exercise or a predominant contribution of parasympathetic activity, which are still intact systems in the TETRA population. The results of this study support the positive role of acute exercise on oral immune function in wheelchair athletes independent of disability type.